2009
DOI: 10.1211/jpp.61.09.0016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yokukansan, a traditional Japanese medicine, on social and aggressive behaviour of para-chloroamphetamine-injected rats

Abstract: These results suggest that yokukansan might have two different effects: an acute effect on social behaviour and a chronic effect on aggressive behaviour. One of the mechanisms of these effects of yokukansan may be related to the agonistic effect on 5-HT1A receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…These results suggest that YKS has a partial agonistic effect on 5-HT1A receptors. More recently, we demonstrated that ameliorative effects of YKS against PCA-induced aggressive behaviors in rats were counteracted by the 5-HT1A receptor antagonist WAY-100635 (Kanno et al, 2009). These in vitro and in vivo findings, taken together, suggest a possibility that the effects of YKS are mediated by a 5-HT1A receptor agonistic effect.…”
Section: Discussionmentioning
confidence: 76%
“…These results suggest that YKS has a partial agonistic effect on 5-HT1A receptors. More recently, we demonstrated that ameliorative effects of YKS against PCA-induced aggressive behaviors in rats were counteracted by the 5-HT1A receptor antagonist WAY-100635 (Kanno et al, 2009). These in vitro and in vivo findings, taken together, suggest a possibility that the effects of YKS are mediated by a 5-HT1A receptor agonistic effect.…”
Section: Discussionmentioning
confidence: 76%
“…We previously demonstrated that yokukansan ameliorated aggressive behavior in rats as effectively as a 5-HT1A receptor agonist (Kanno et al 2009). Subsequent in vitro binding studies showed that yokukansan had a partial agonistic effect on 5-HT1A receptors, which was attributed to GM in Uncaria hook, a galenical constituent of yokukansan (Terawaki et al 2010;Nishi et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Yokukansan ameliorated the aggressive behavior as effectively as a serotonin (5-HT)1A receptor agonist or 5-HT2A receptor antagonist (Kanno et al 2009). From these results, we hypothesized that this effect of yokukansan may be due to 5-HT1A receptor agonism or 5-HT2A receptor antagonism.…”
Section: Introductionmentioning
confidence: 99%
“…The dose of YKS (1 g/kg) in the present study was determined according to the results of our previous studies, in which treatment with 1 g/ kg of YKS significantly ameliorated aggressiveness, impaired sociality, or anxiety in animal models of neuropsychiatric disorders. [8][9][10]30) AIMs were evaluated as described previously 13,31) with modifications. The rats in each group were observed for 1 min every 10 min for 180 min after the injection of L-DOPA.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10] An in vitro competitive binding assay showed that YKS did not bind to various DA receptor subtypes. However, YKS ameliorated anxiety and decrease in extracellular DA concentrations in the prefrontal cortex (PFC) of aged rats.…”
mentioning
confidence: 99%